PROCESS CAPABILITY INDEX-BASED CONTROL CHART FOR VARIABLES - Adeoti, Olatunde Adebayo; Olaomi, John Olutunji (The South African Journal of Industrial Engineering, 2017)
This paper proposes a process capability index-based control chart for variables using the Downton estimator with a specified Cp value. The proposed chart is able to address the issue of control and capability simultaneously. We also provide a control chart constant to construct the process capability index-based control chart. A numerical example is presented to demonstrate the application of the proposed chart, and the effect of non-normality is discussed. The result shows that the proposed control chart performs better in monitoring and assessing processes, and eliminates the usual two-stage procedure reflected in the literature.